Abnormal psychology - Coriat, Isador H. (Isador Henry), 1875-1943 (International library of psychology., 1910)
Abnormal Psychology provides a thorough grounding for undergraduate students with little or no previous knowledge of this complex area of psychology. The focus is on clinical descriptions, using illustrative case studies, and on the implications of the major theoretical perspectives and relevant empirical evidence for clinical treatment.